3D robocasting magnesium-doped wollastonite/TCP bioceramic scaffolds with improved bone regeneration capacity in critical sized calvarial defects. Issue 16 (4th April 2017) - Shao, Huifeng; Liu, An; Ke, Xiurong; Sun, Miao; He, Yong; Yang, Xianyan; Fu, Jianzhong; Zhang, Lei; Yang, Guojing; Liu, Yanming; Xu, Sanzhong; Gou, Zhongru
Abstract : 3D robocasting of CSi-Mg10/TCP15 bioceramic scaffolds with high bone regeneration capacity in rabbit calvarial defects were realized for tissue engineering applications. Abstract : Using artificial biomaterials in bone regenerative medicine for highly efficient osteoconduction into the bone defect to decrease the bone healing time is still a challenge. In this research, magnesium (Mg)-doped wollastonite (∼10% Mg was substituted for calcium (Ca) in β-CaSiO3 ) (CSi-Mg10) bioceramic scaffolds with ultrahigh mechanical strength were fabricated using ceramic ink writing three dimensional (3D) printing. To evaluate the potential of other additives on the new bone regeneration efficiency, β-tricalcium phosphate (β-TCP) was introduced to the CSi-Mg10 ceramic ink at a concentration of 15% and the biphasic bioceramic scaffolds (CSi-Mg10/TCP15) were also fabricated using 3D printing. The mechanical characterization indicated that introduction of β-TCP led to nearly 50% mechanical decay, although the effect of the two heating schedules (one- and two-step sintering) on the compressive and flexural strengths of the scaffolds was significantly different. The bone regeneration results in critical sized calvarial defect of rabbits showed that the CSi-Mg10/TCP15 scaffolds displayed a markedly higher osteogenic capability than those on the CSi-Mg10 and β-TCP scaffolds after eight weeks, and reached ∼35% new bone tissue regeneration at 12 weeks postoperatively. These findings demonstrate that the CSi-Mg10/TCP15 bioceramic scaffolds can be well suited for stimulating in situ bone regeneration and for use in tissue engineering applications.